Analisis Efektivitas Mesin pada Divisi Pengalengan Jamur Di PT XYZ Menggunakan Metode Overall Equipment Effectiveness - Aditya Haradito; Iman Sabarisman; Satria Bhirawa Anoraga (Jurnal Nasional Teknologi Terapan (JNTT), 2019)
PT XYZ is one of the food canning companies in Indonesia. Nowadays, many companies are looking up for the alternatives to increase the company revenue by making a continous improvement in every process. This study has three aims to be achieved. First, knowing the value of availability rate, performance rate, and quality rate. Second, to determine the major cause which affecting the effectiveness value of the production machine. Third, to obtain the alternatives improvement to increase the machine effectivity. Overall Equipment Effectiveness (OEE) is a method to determine the effectiveness level of equipment utilization. The OEE method is known as one of the program applications of Total Productive Maintenance (TPM). This study measures the value of OEE in the production line of mushroom canning within two months. The values of this study are, availability rate is 89.99%, performance rate is 65.13%, and quality rate is 99.76%. From those data, the obtained calculation value of OEE is 58.71%, it shows that it has not reach yet the best practice (85%) and need an improvement. The Losses in PT XYZ are breakdown losses, setup and adjustment losses, idle and minor stoppage losses, and defect losses. The alternatives improvement are tightening the maintenance schedule, as well as inspection before and after use on the machine. This maintenance is supported by a focus on the TPM pillar of self-improvement, which changes the workers’ mindset, to change the mindset of the workers there should be an education and training to improve the ability of workers.